Vegetation around Tiga Warna Lake, Kelimutu National Park, Ende, Flores, East Nusa Tenggara - DEDEN MUDIANA; SUHARMONO SUHARMONO; I MADE RAHARDJA PENDIT; I WAYAN MUDARSA (Society for Indonesian Biodiversity, 2003)
Vegetation around Danau Tiga Warna, Kelimutu National Park was dominated by Vaccinium varingiaefolim (Blume) Miq. Species of fern, Selluguea triloba (Houtt.) M.G. Price and Gleichenia linearis (Burm.) Clarke were abundant in this location. Tripogon exiguus Buesee as belongs poaceae family, also find abundant. Condition of vegetation around Kawah Kelimutuwill discribe in this paper.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey word: vegetation, Danau Tuga Warna, Taman Nasional Kelimutu.